Pengaruh Penambahan Zat Aditif Anti Striping (WETFIX-BE) Pada Kinerja Campuran Aspal Beton (AC-WC) - Al Paris, Fadhil Qodri; Yamali, Fakhrul Rozi; Handayani, Elvira (Universitas Batanghari, 2024)
The asphalt concrete layer is the top layer of road pavement construction which is in direct contact with vehicle wheel loads and the influence of weather. One type of asphalt concrete layer is Asphalt Concrete – Wearing Course (AC–WC). Asphalt functions as an aggregate adhesive. In asphalt concrete mixtures it is very important to maintain its characteristics. During the maintenance period, the mixture will easily experience striping or peeling of the asphalt from the aggregate. To maintain and improve the properties of asphalt, one way is to use an anti-striping additive, this additive is Wetfix-Be, which is a compound that contains chemicals. Anti-peeling materials are only used if the residual Marshall stability value (IRS-Index of Retained Stability) or the Indirect Tensile Strength Ratio (ITSR) value of the asphalt mixture before adding the anti-peeling agent is less than required. If an anti-flaking agent must be used then before the anti-flaking agent is added to the mixture, the residual marshall stability (after 24 hour immersion, 60 °C) must be at least 75%.